2008
DOI: 10.1021/jp804355z
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electronic Properties of Au and Au2on an MgO(100) Surface: A DFT Cluster Embedding Approach

Abstract: The structural and electronic properties of Au and Au2 adsorbed on five coordinated oxygen and magnesium regular terrace sites, on the neutral Fs color center (oxygen vacancy containing two electrons), and on the charged Fs + color center (oxygen vacancy containing one electron) of the MgO(100) surface have been investigated using a density functional theory cluster embedding approach. Two types of calculations have been performed. In one, we optimized and calculated the energetics of the systems using a gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…In addition, the presence of the vacancy and impurity point defects on the h-BN surface results in a drastic change in the charge state of the trapped Au and Au 2 and hence also influences the catalytic activity of the supported gold particles. Although it is well established that F-center defects in metaloxides can promote catalytic activity of gold clusters via the charge transfer, 19,35,74 to the best of our knowledge the similar effect for gold clusters supported on the h-BN surface has not been studied yet. In the case of O 2 adsorption on free Au, the Bader charge localized on O 2 is −0.19e.…”
Section: ■ Theoretical Resultsmentioning
confidence: 95%
“…In addition, the presence of the vacancy and impurity point defects on the h-BN surface results in a drastic change in the charge state of the trapped Au and Au 2 and hence also influences the catalytic activity of the supported gold particles. Although it is well established that F-center defects in metaloxides can promote catalytic activity of gold clusters via the charge transfer, 19,35,74 to the best of our knowledge the similar effect for gold clusters supported on the h-BN surface has not been studied yet. In the case of O 2 adsorption on free Au, the Bader charge localized on O 2 is −0.19e.…”
Section: ■ Theoretical Resultsmentioning
confidence: 95%
“…One Au atom is bound to an oxygen surface atom at a distance of 2.166Å, while the dimer bond length remains practically unchanged (2.507Å) compared to the gas-phase structure (2.511Å), in good agreement with previous theoretical results. 11,49,52,[96][97][98] The ground state of both gas-phase and supported Au 2 is a singlet. Furthermore, due to the strong attractive interaction at the F s center, the most stable Au dimer configuration is tilted toward an Mg surface atom (67 • to the surface normal), with an elongated dimer bond length of 2.70 A, compared to the dimer supported on the pristine surface (see Fig.…”
Section: Supported Au N Clusters Structural Motifsmentioning
confidence: 99%
“…Concerning the catalytic activity, it was observed that when the particles are supported, typically on an oxide surface, their electronic structure can be strongly affected by the support which in turns modifies the surface reactivity [8,9]. For example, it is well known that the interaction with an oxide can cause charging of Au aggregates [10][11][12][13][14][15][16][17][18][19]. When the supported particles are composed by two different metals, the composition and segregation properties are also important in determining their catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…It presents different type of defects which are relatively simple to model. The deposition of coinage metal atoms and clusters on regular and defective MgO(1 0 0) surface was recently studied from DFT calculations [11][12][13][14][15][16][17][18][19]21]. Among the different type of defects present on terrace, the neutral O-vacancy (F s centers) has been widely analyzed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation